Coordinated gene expression and hormonal fluxes dictating ginsenoside Rb3 biosynthesis in floral development of Panax notoginseng - Can Wang; Hongwei Sun; Yuling Yang; Cuixian Peng; Yuan Liu; Yonghong Tao (BMC Plant Biology)
Abstract Background Panax notoginseng (PN) is a medicinal plant containing essential ginsenosides. Given the therapeutic significance of ginsenosides, we delved into the mechanisms of ginsenoside Rb3 biosynthesis in PN flowers. We examined this process from the pre-differentiation stage to the end of flowering, aiming to uncover the biochemical pathways underlying ginsenoside production in PN. Results Budding stage (T2) was found critical for enhanced Rb3 production. Transcriptomic analysis revealed a marked shift in gene expression beginning at T2, with upregulation in pathways associated with secondary metabolite production. Gene set enrichment analysis (GSEA) illuminated the upregulation of genes involved in terpenoid backbone biosynthesis, amino acid degradation, and terpenoid modifications, specifically at T2. We correlated the fluctuating hormone levels with the activity of the transcription factor MYC2 to underscore hormonal influence on ginsenoside biosynthesis. Biosynthesis pathway reconstruction revealed the dominance of the mevalonate pathway. Critical enzymes such as ACAT, PPDS, DDS, and LUP4 were vital in precursor biosynthesis and modification. Notably, key genes such as HMGCS, FDPS, and DDS, as well as transcription factors MYC2, MYB124, and MYB61.1, showed a concerted surge in activity at T2. Conclusions These findings provide insights into the complex gene networks and molecular pathways that regulate ginsenoside biosynthesis, thereby promoting the medicinal properties of PN.